A3_6 Could it really be cheese? - Leversha, Thomas; Flood, Laura; Holland, Katie; Manley, Max (Physics Special Topics, 2022)
This paper investigated the material properties of the moon in the film ”Wallace and Gromit A Grand Day Out”. We conclude that it is possible for the moon to be comprised of cheese, demonstrated by a kinetic friction coefficient of 0.16 which is comparable to a lightly lubricated metal-rough surface boundary much like skis against a crumbly cheese.